2022
DOI: 10.1101/2022.09.09.507373
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Vaping Increase the Likelihood of SARS-CoV-2 Infection? Paradoxically Yes and No

Abstract: Data on the relationship between electronic cigarettes (ECs) and SARS-CoV-2 infection are limited and contradictory. Evidence indicates that EC aerosols or nicotine increase ACE2, SARS-CoV-2 virus receptors, which increase virus binding and susceptibility. Our objectives were to determine if EC aerosols increased SARS-CoV-2 infection of human bronchial epithelial cells and to identify the causative chemical(s). A 3D organotypic model (EpiAirway) in conjunction with air liquid interface (ALI) exposure was used … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…This infection system has been adapted to other cell types and species ( Song et al, 2023 ). Pseudotyping has been used previously to study virus-host receptor binding ( Wang et al, 2008 ; Lu et al, 2014 ; Phandthong et al, 2022 , 2023 ) and can be applied to Mv1Lu cells, which are a robust in vitro model for studying coronavirus infection in mink.…”
Section: Discussionmentioning
confidence: 99%
“…This infection system has been adapted to other cell types and species ( Song et al, 2023 ). Pseudotyping has been used previously to study virus-host receptor binding ( Wang et al, 2008 ; Lu et al, 2014 ; Phandthong et al, 2022 , 2023 ) and can be applied to Mv1Lu cells, which are a robust in vitro model for studying coronavirus infection in mink.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudotyping is used to study binding of the viral protein to the host cell receptors and has been successfully used in previous Coronavirus studies (Hurlburt et al, 2020;Lu et al, 2014;Phandthong et al, 2022aPhandthong et al, , 2022b. Furthermore, SARS-CoV-2 pseudoparticles can be generated in a BSL-2 biosafety cabinet, which is a major advantage over using live virus.…”
Section: Commentary Background Informationmentioning
confidence: 99%
“…Most prior zoonotic studies on this pathway have focused on ACE2 conservation and ACE2 affinity to predict the host range of SARS-CoV-2 (Damas et al 2020;Sun et al 2021). More recent SARS-CoV-2 studies have also demonstrated the importance of testing TMPRSS2 activity as well as expression (Shrimp et al 2020;Phandthong et al 2022;Phandthong et al 2023). In our study, TMPRSS2 inhibitors did block enzymatic activity, but they did not reduce SARS-CoV-2 infection, supporting the conclusion that this pathway was not important in Mv1Lu cells.…”
Section: Small Molecule Inhibitor Screening Showed That Endocytosis I...mentioning
confidence: 99%